Ability of Staphylococcus spp. Isolated from Meningitis Patients to Adhesion - Luma Abdulhady Zwain (Journal of Global Pharma Technology, 2016)
A total 248 clinical samples of cerebrospinal fluid (CSF) were collected from meningitis patients, for the period of July to October 2018 from the Child Protection Teaching Hospital in the Medical City Compound in Baghdad. All isolates were identification depending on macroscopic, microscopic, biochemical tests and definite with Vitek-2 compact system. The results showed a growth in 42 samples.  Sixteen isolates of Staphylococcus spp. were obtained from samples .The number of the percentage of isolates according to species as follow: 7/16) 44%) of S. epidermidis, 3/16 (19%) of S. hominis, 3/16)19%) of S. haemolyticus, 2/16 (12%) of S. aureus, 1/16 (6%) of S.warneri. The ability of isolates on adhesion were studied and the results showed the use polystyrene plates, that the number of adherent cells of S. epidermidis was 230 cells / field, S. hominis was 62 cells / fields, whereas S. aureus was 3 cells / field, while in S. haemolyticus >300 cells / field, finally the number of cells in each field of S.warneri reached 40 cells / field.  In use epithelial cells (Vero cell line), the results of our current study we observed that, the number of all Staphylococcus spp. in zero dilution were >300 cfu. and  S. epidermidis, S .hominis, S. aureus, S. haemolyticus , S. warneri were (85,120,>300 , ,>300  ,>300 )cfu respectively   at 1:10 dilution, while  at the dilution 1:100 the number were(9,30, >300, >300 ,292)cfu respectively.Keywords: Staphylococcus spp., Meningitis, Adhesion.